Clinical Impact of Cardiovascular Magnetic Resonance in Cancer Patients With Suspected Cardiomyopathy - Heidari-Bateni, Giv; Durand, Jean-Bernard; Iliescu, Cezar; Gladish, Greg; Deswal, Anita; Patel, Amit R.; Kim, Peter; Song, Juhee; Hassan, Saamir; Palaskas, Nicolas; Baldassarre, Lauren A.; Bucciarelli-Ducci, Chiara; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To assess the clinical impact of Cardiovascular Magnetic Resonance (CMR) in clinical decision making of cancer patients with a suspected cardiomyopathy in a tertiary cancer center. Background: Cardiomyopathies of diverse etiologies are frequently encountered in a Cardio-Oncology practice. The clinical impact of CMR after a presumptive diagnosis of cardiomyopathy has not been studied in cancer patients. Methods: We reviewed data on cancer patients with presumptive diagnosis of cardiomyopathy who underwent CMR in a tertiary cancer center. The clinical impact of CMR was defined as either change in clinical diagnosis or management post CMR results. Univariate and multivariate logistic regression models were used to assess whether any of the baseline characteristics were predictive of the clinical impact of CMR. Results: A total of 110 consecutive patients were identified. Clinical impact of CMR was seen in 68 (62%) patients. Change in the clinical diagnosis and management was seen in 56 (51%) and 41 (37%) of patients, respectively. The most common change was prevention of endomyocardial biopsy in 26 patients (24%). Overall, patients with higher left ventricular ejection fraction (LVEF) by echocardiography (echo), clinical impact was influenced more by CMR (LVEF of 37.2 ± 12.3% vs. 51.5 ± 11.6%, p < 0.001). Cancer diagnosis of multiple myeloma was associated with change in the management post CMR (adjusted OR of 25.6, 95% CI 4.0–162.4, p = 0.001). Suspicion of infiltrative cardiomyopathy was associated with a higher likelihood of change in diagnosis. Having an LVEF≥40 by echo was associated with change in diagnosis and management by CMR. Conclusions: Utilization of CMR has a significant clinical impact in cancer patients with suspected cardiomyopathy. Patients with cancer diagnosis of multiple myeloma, suspicion of infiltrative cardiomyopathy and those with higher LVEF by echo seem to benefit more from CMR.